2001
DOI: 10.1128/mcb.21.20.7105-7114.2001
|View full text |Cite
|
Sign up to set email alerts
|

The Modified Human DNA Repair EnzymeO6-Methylguanine-DNA Methyltransferase Is a Negative Regulator of Estrogen Receptor-Mediated Transcription upon Alkylation DNA Damage

Abstract: Cell proliferation requires precise control to prevent mutations from replication of (unrepaired) damaged DNA in cells exposed spontaneously to mutagens. Here we show that the modified human DNA repair enzyme O 6 -methylguanine-DNA methyltransferase (R-MGMT), formed from the suicidal repair of the mutagenic O 6 -alkylguanine (6RG) lesions by MGMT in the cells exposed to alkylating carcinogens, functions in such control by preventing the estrogen receptor (ER) from transcription activation that mediates cell pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
42
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(43 citation statements)
references
References 41 publications
1
42
0
Order By: Relevance
“…Upon the repair of O 6 -methylguanine adducts, MGMT changes its conformation to expose its LXXLL motif and binds the estrogen receptor (ER), blocking ER from binding transcription coactivators containing the same motif [59] . MGMT 143Val may affect the regulation of ER-dependent signaling, as MGMT Ile143Val lies in close proximity to the conserved ER-interacting helix.…”
Section: Discussionmentioning
confidence: 99%
“…Upon the repair of O 6 -methylguanine adducts, MGMT changes its conformation to expose its LXXLL motif and binds the estrogen receptor (ER), blocking ER from binding transcription coactivators containing the same motif [59] . MGMT 143Val may affect the regulation of ER-dependent signaling, as MGMT Ile143Val lies in close proximity to the conserved ER-interacting helix.…”
Section: Discussionmentioning
confidence: 99%
“…MGMT removes alkyl adducts from the O 6 position of guanine, and then inactivates the proliferation of cells with damaged DNA. Therefore, it can protect cells from alkylating damages and maintain genomic integrity [15] . Our results suggest that the epigenetic alteration in MGMT promoter may confer an increased risk of alkylating agentinduced colorectal carcinogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, in adherent cells, no effect on cell growth is seen whether they express low or very high MGMT levels, indicating that MGMT itself is not linked to regulation of proliferation. In addition, although MGMT is frequently upregulated in cells in more aggressively growing tumours [22], there is no evidence that MGMT has a direct stimulatory or inhibitory effect on tumour growth, although there is one report that the methylated (inactivated) MGMT can bind to the oestrogen receptor and affects growth rate [23]. It has also been shown that, in CD34 ?…”
Section: The Dna Repair Protein Mgmtmentioning
confidence: 99%